2021
DOI: 10.1021/acsnano.0c10647
|View full text |Cite
|
Sign up to set email alerts
|

Subwavelength-Polarized Quasi-Two-Dimensional Perovskite Single-Mode Nanolaser

Abstract: When approaching the subwavelength or deep subwavelength scale, there is a fundamental trade-off between the ultimate shrinking size and the performance for miniaturized lasers. Herein, to overcome this trade-off, we investigated the excitonic gain nature of quasi-two-dimensional (quasi-2D) perovskites and revealed that both singlet excitons and polarons would make nearly the entire contribution within ∼50 ps to a high net gain of 558 cm–1. Inspired by the gain characteristic, we successfully shrank the quasi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 56 publications
0
42
0
Order By: Relevance
“…29 The carrier dynamics and transport in mixed-phase layered perovskites play a key role in enhancing the performance of 2D optoelectronic devices. 30,31 The average carrier lifetime for the DJ lead iodide perovskites with organic diamine is twice that for the RP architectures. 32 However, there are discrepancies in the time scales and the transport mechanisms for DJ and RP perovskites thin films.…”
Section: Introductionmentioning
confidence: 99%
“…29 The carrier dynamics and transport in mixed-phase layered perovskites play a key role in enhancing the performance of 2D optoelectronic devices. 30,31 The average carrier lifetime for the DJ lead iodide perovskites with organic diamine is twice that for the RP architectures. 32 However, there are discrepancies in the time scales and the transport mechanisms for DJ and RP perovskites thin films.…”
Section: Introductionmentioning
confidence: 99%
“…182 Most recently, Liu et al shrank the quasi-2D perovskites laser to the deep-subwavelength scale with 50 nm, which was the smallest room temperature alldielectric laser. 183 They revealed the contribution from excitons and polarons to the high optical gain, which provided an insight into the design of next-generation integrated laser sources. Qin et al 171,184 found that the triplet excitons in hybrid quasi-2D perovskite have a lifetime up to 1 μs, which might cause the disappearance of the laser.…”
Section: Othersmentioning
confidence: 99%
“…In recent years, halide perovskite materials, especially all-inorganic perovskite materials (CsPbX 3 , X = Br, Cl, and I) have attracted much attention in light-emitting diodes (LEDs), [1][2][3][4] lasers, [5,6] solar cells, and other related optoelectronic devices owing to their excellent properties. [7,8] Especially in the field of luminescence, it shows many advantages, such as narrow full-width at half-maximum, high photoluminescence (PL) quantum yield, and low-cost solution process.…”
Section: Introductionmentioning
confidence: 99%